Reflections on Metaphors for Learning Design - Dobozy, Eva; Dalziel, J. (Routledge, 2016)
Metaphors are commonly used to help explain complex phenomena. Hence, they have been accepted as a simple yet effective cognitive tool which enables the transfer of meaning between dissimilar domains. The literal interpretation of the term metaphor is transfer. Tracing the etymology of the term, Stern provides the following definition: Middle English metaphor, from Old French metaphore, from Latin meatphora, from Greek, transference, metaphor, from metapherein, to transfer: meta-, meta- + pherein, to carry. [The American Heritage Dictionary (2000, p. 1134), cited in Stern (2009, p. 81)].